Analisis Implementasi Pelayanan Jamaah Umrah pada Arabia Nusantama Raya Travel Padang Menurut Perspektif Bisnis Syariah - Al Rozali; Andis Febrian (Darul Yasin Al Sys, 2026)
Although the service quality of Umrah travel agencies has received attention in various previous studies, studies that specifically discuss the implementation of services based on the RATER dimensions in certified Umrah travel agencies in West Sumatra remain limited. This study aims to analyze the implementation of Umrah pilgrim services at PT Arabia Nusantama Raya Travel Padang from the perspective of Sharia business. This study used a qualitative approach with field research techniques. The research informants consisted of the management and personnel of PT Arabia Nusantama Raya Travel Padang. Data were collected through observation, in-depth interviews, and documentation and were then analyzed qualitatively. The results show that service implementation overall has been carried out fairly well across the five service quality dimensions, namely reliability, responsiveness, assurance, empathy, and tangibles. The services provided encouraged pilgrims to feel safer and to have greater trust in the company. However, continuous improvement is still needed, particularly in the effectiveness of the Umrah ritual guidance schedule and the formalization of the post-return evaluation system. The conclusion of this study emphasizes that Umrah pilgrim services based on the RATER dimensions from the perspective of Sharia business need to be managed consistently through strengthening service quality, pilgrim trust, and a more systematic service evaluation.